Comparison of Pain Scores between Intravenous versus Rectal Acetaminophen in Children Undergoing Tonsillectomy - Udesh Kumar, Kainat, Ravi Kumar, Mahendar, Bahram Khan, Hiranand (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Post-operative tonsillectomy pain is widely observed especially among children which leads to longer hospitalization, slower recovery, eating disorder and continuation of IV fluids ingestion. Objective: To compare mean pain scores between intravenous versus rectal acetaminophen in children undergoing tonsillectomy. Study Design: Randomized controlled trial Place and Duration of Study: Department of Anesthesiology, Surgical Intensive Care & Pain Management, Civil Hospital Karachi, Dow University of Health Sciences, Karachi from 15th July 2015 to 14th January 2016. Methodology: Seventy eight patients with American Society of Anesthesiologist Physical Status (ASA) I and II having age 4-10 years of either gender presented with chronic tonsillitis and duration of disease of more than or equal to one year and underwent elective surgeries (tonsillectomy) were enrolled. Patients were randomly allocated by computer generated random number in two groups; group A received intravenous acetaminophen and group B received rectal acetaminophen. In group A, intravenous acetaminophen 10mg/kg was given and in group B, rectal acetaminophen 15mg/kg was given. Postoperative pain was assessed after 4 hour in ward based on CHIPPS criteria. Results: Mean age was 6.69 2.12 years in intravenous group whereas 5.94±1.97 years in rectal group (P=0.114). Mean duration of disease in intravenous group was 1.82±0.72 years whereas in rectal group, it was 2.07±0.62 (P=0.097). Mean pain score in intravenous group was 2.65±0.05 and 1.97±0.01in rectal group (P=0.001). Conclusion: Significant difference was observed in mean pain scores between intravenous versus rectal acetaminophen in children undergoing tonsillectomy Keywords: Tonsillectomy, Intravenous versus rectal acetaminophen, Pain scores